2015
DOI: 10.1116/1.4926547
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 20 nm silver nanoparticles synthesized with and without a gold core: Structure, dissolution in cell culture media, and biological impact on macrophages

Abstract: Widespread use of silver nanoparticles raises questions of environmental and biological impact. Many synthesis approaches are used to produce pure silver and silver-shell gold-core particles optimized for specific applications. Since both nanoparticles and silver dissolved from the particles may impact the biological response, it is important to understand the physicochemical characteristics along with the biological impact of nanoparticles produced by different processes. The authors have examined the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 81 publications
3
47
0
Order By: Relevance
“…This may suggest an inflammatory response to IT instillation of AgNP that does not remain localized to the lungs. The apparent interactions of AgNP with macrophages observed in this study and reported elsewhere [12,23,3638] may promote cytokine release in the lungs resulting in a systemic inflammatory response through these cytokines. AgNP have been demonstrated to interact with mast cells and induce degranulation [8].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This may suggest an inflammatory response to IT instillation of AgNP that does not remain localized to the lungs. The apparent interactions of AgNP with macrophages observed in this study and reported elsewhere [12,23,3638] may promote cytokine release in the lungs resulting in a systemic inflammatory response through these cytokines. AgNP have been demonstrated to interact with mast cells and induce degranulation [8].…”
Section: Discussionsupporting
confidence: 69%
“…This may result from slowed pulmonary clearance of particles administered by instillation compared to inhalation [45] or the dissolution and formulation of other NP or salt participates [24,36,46] The contribution of silver ions to the observed toxicity observed remains a possible mechanism. It has been reported that 20 nm citrate capped AgNP quickly dissolutes in water however, this dissolution can be slowed in the presence of dipalmitoylphosphatidylcholine a componenet of surfactant [23,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particles had been stabilized by sodium citrate and were also covered, as should be expected, by a thin layer of adventitious hydrocarbon. Scanning transmission electron microscopy (STEM) analysis of a series of particles showed that the core/shell Au/Ag NPs, described previously, 7 had a polydispersed size distribution, often had slightly non-spherical shapes, and had Au cores that were frequently off-center. The STEM measurements were used to determine average dimensions of the Au core and Ag shell as well as the distribution of deviations from that average.…”
mentioning
confidence: 73%
“…Further alterations in silver nanoparticle dissolution due to modifications in their physicochemical properties have been shown to influence toxicological outcomes in vitro [54]. The addition of the biocorona may alter this dissolution resulting in the stabilization or destabilization of the nanoparticle structure.…”
Section: Challenges Presented By the Nanoparticle-biocoronamentioning
confidence: 99%